Gender Differences and Dynamics in Competition: The Role of Luck. - Gill, D; Prowse, V (IZA, 2010)
We present experimental evidence which sheds new light on why women may be less competitive than men. Specifically, we observe striking differences in how men and women respond to good and bad luck in a competitive environment. Following a loss, women tend to reduce effort, and the effect is independent of the monetary value of the prize that the women failed to win. Men, on the other hand, reduce effort only after failing to win large prizes. Responses to previous competitive outcomes explain about 11% of the variation that we observe in women’s efforts, but only about 4% of the variation in the effort of men, and differential responses to luck account for about half of the gender performance gap in our experiment. These findings help to explain both female underperformance in environments with repeated competition and the tendency for women to select into tournaments at a lower rate than men.